Análise da influência do teor de fibras de aço relacionado ao excesso de volume de pasta do concreto de ultra-alto desempenho - Cury, Ana Carolina Seguro (2024)
Aiming meet the demands of civil construction, Ultra-High-Performance Concrete (UHPC) has been the subject of materials research for over three decades. It exhibits remarkable mechanical and physical characteristics such as strength, ductility, and workability. Its composition differs from conventional concretes, including components like active silica, quartz powder, superplasticizer additive, and metallic fibers, in addition to a low water/binder ratio. The addition of fibers improves the toughness, ductility, and strength of the concrete, however, it can cause manufacturing defects, such as air entrapment and loss of workability, requiring appropriate repair methods. Therefore, it is important to analyze the ideal fiber content in relation to the volume of paste to obtain a UHPC with better performance and workability. This research aims to analyze the influence of the steel fiber content relative to the excess volume of paste in UHPC, assessing its performance in both fresh and hardened states. The research contributed to optimizing the content of metallic fibers and the volume of paste in UHPC compositions, aiming to define the influence of fibers and paste to obtain the best concrete properties. Thus, the experimental program of this dissertation consisted of establishing the appropriate choice of materials and obtaining the mix design of ultrahigh-performance concrete through Alfred, Toufar, and wet packing methods. The minimum paste content necessary to hydrate the grains was calculated, and additional amounts of materials were determined for mixes with 20%, 40%, 60%, and 80% excess paste. The mix designs were manufactured and analyzed in both fresh and hardened states, including different contents of metallic fibers, ranging from 0% to 5%, limited by the maximum and minimum spread allowed by the slump flow test. Tests were conducted to evaluate the spread, workability, and mechanical strength of the UHPC. After analyzing the results, it was observed that the influence of the fibers acts to reduce the spread of the mixture in the fresh state and to decrease the compressive strength in the hardened state. Regarding the excess paste, in the fresh state tests, it was noted that as the excess paste increased, the mixture became more fluid, improving its workability. However, for the tests in the hardened state, there was no statistical difference between the mixes with different paste contents.